The role of specialisation in the promotion of young football talents: A person-oriented study - Zibung, M.; Conzelmann, A. (European Journal of Sport Science, 2013)
This paper investigates the controversial question whether it is more effective to promote specialisation in a specific sport at the beginning of a career or whether to encourage a broad range of sports when promoting competitive sports talents in order for them to achieve a high level of performance in adulthood. The issue of promoting talents depends on human developmental processes and therefore raises developmental scientific questions. Based on recent, dynamic-interactionist concepts of development, we assume a person-oriented approach focussing on the person as a whole rather than individual features. Theoretical considerations lead to four interacting factors being summarised to form a subsystem: childhood training. The relative weights of these factors lead to patterns. By relating these to a performance criterion at the age of peak performance, particularly promising developmental patterns may be identified. One hundred fifty-nine former Swiss football talents were retrospectively interviewed about their career and the data analysed using the LICUR method. Two early career patterns were identified as having a favourable influence on adult performance. Both are characterised by an above-average amount of in-club training. One pattern also exhibits an above-average amount of informal football played outside the club, the other above-average scores for activity in other sports. Hence, comprehensive training and practice inside and outside the club form the basis for subsequent football expertise.